The pelvic recurrences of rectal cancers - Urdinarán, Ricardo (Cirugía del Uruguay, 2021)
The author discusses the general aspects of pelvic recurrence of cancer of the rectum with an analysis of the clinical material available. Etiopathologically the fundamental mechanism in recurrences is retrograde intramural diffusion and implantation in the mucous membrane. Prevention of recurrence can be di vided in two successive stages: during treatment of the primary tumor and in postoperatory control. Surgical and radiotherapeutical aspects in the treatment of pelvic recurrences are analyzed; the combination of both types of treatment applied systematically is of great importance.